Lek som musisk kommunikasjon - Hovik, Lise (Peripeti, 2011)
Through her own practice-led research into interactive theatre for children in the performance, De Røde Skoene (eng.: The Red Shoes, Hovik 2008), and critical reflections on theories of play, Lise Hovik proposes a concept of play as communicative musicality. This form of play works as a “rhythmical transparency” between the performers’ improvisations and children’s (re-)actions. She presents play heuristic as a possible resource for the development of theatre for the youngest children.